William Gilbert Gosling and the Establishment of Commission Government in St. John's, Newfoundland, 1914 - Baker, Melvin (Urban History Review / Revue d'histoire urbaine)

(untitled) (Urban History Review / Revue d'histoire urbaine, 1981)
The St. John's commercial community took little interest in the administration of the Municipal Council from the city's incorporation in 1888 to 1913. Most prominent merchants were pressed for time because of their businesses; they preferred either to sit in the prestigious Legislative Council or, occasionally, to seek election to the House of Assembly. Under the terms of the 1888 Municipal Act, membership in these legislative bodies gave the merchants considerable control over the city's finances and management.The Municipal Council constantly experienced financial difficulties because of insufficient revenue for improvements. The aim of the civic reform movement organized in December, 1913, by William Gilbert Gosling, the President of the Board of Trade, was to devise means of obtaining additional revenue for municipal improvements. In effect, this meant increasing the property tax, a prospect the city's merchants were forced to accept to achieve an improved water supply for greater fire protection. The additional revenue was to be used also to provide better housing for the poor and to improve public health and sanitary conditions. Early in 1914 the Board of Trade was successful in having the elective council replaced by an appointed commission of businessmen. This commission was intended to administer the city for one year from July 1, 1914, re-organize the various municipal departments, and draft a new municipal charter that would give the council the revenue it required. Gosling's initiative set in motion the events that led to the charter of 1921, the basis of present-day municipal government in St. John's.